Differential Impact of Pictorial Health Warnings on Combustible and Smokeless Tobacco: A Longitudinal Policy Review and Trend Analysis in Nepal - Sapkota, Kiran; Dhital, Shalik Ram (Journal of Bharatpur Hospital, 2025)
Study BackgroundThe WHO Framework Convention on Tobacco Control (FCTC) has its roots in the Pictorial health warnings (PHWs). There has been an increase of PHW in Nepal from 75% to 90%, thus making this a unique policy that needed to be evaluated. The aim of this study was to analyze the evolution of warning policies and to examine how the policies are associated with smoking, having in mind the current prevalence of smokeless tobacco (SLT).MethodsThis study utilized a longitudinal approach to conduct a policy review by examining Nepal’s national legislation, government directives, as well as court records to track the timeframe of implementing Pictorial Health Warning in Nepal. The trend of tobacco usage was analyzed using a STEP-wise approach to surveilling non-communicable diseases. Data used in this analysis comprised of three years, which are six-year apart: 2007, 2013, and 2019.ResultsThe regulatory framework of Nepal gradually evolved from 75% (enacted in the year 2021 and implemented in 2014) to 90% (implemented in 2015). This culminated in the directive for plain packaging in 2025. Notably, the prevalence of smoking significantly dropped from 26.2% in 2007 to 17.1% in 2019. On the other hand, there was a minimal shift in the usage of the smokeless tobacco. Whereas the usage of smokeless tobacco prevalence was at 18.6% in 2007, this prevalence dropped by only 0.3% (up to 18.3%) in 2019.ConclusionFrom this study, the expansion of pictorial health warning was seen to be related to the decrease in cigarette smoking. No significant relationship was noted between pictorial health warnings and the use of smokeless tobacco. These findings show that tobacco packaging interventions are both effective and sometimes inadequate in influencing different forms of tobacco usage. This study has revealed the need for a comprehensive strategy for tobacco control even as Nepal is going to implement the full plain packaging policies.